A dual marker label free electrochemical assay for Flavivirus dengue diagnosis - Santos, Adriano [UNESP]; Bueno, Paulo R. [UNESP]; Davis, Jason J. (Elsevier, 2018)
Dengue is a RNA viral illness of the genus Flavivirus which can cause, depending on the pervasiveness of the infection, hemorrhagic dengue fever or dengue shock syndrome. Herein we present an electrochemical label free approach enabling the rapid sensitive quantification of NS1 and IgG (supporting an ability to distinguish primary and secondary infections). Using a bifunctional SAM containing PEG moieties and a tethered redox thiol, both markers are detectable across clinically relevant levels by label free impedance derived redox capacitance. A subsequent frequency specific immittance function approach enables assaying (within seconds) with no impairment of analytical quality (linearity, sensitivity and variance).
Keywords: Biosensor; Dengue; Electrochemical capacitance spectroscopy; Electrochemical immittance analysis; IgG; Molecular diagnostics; NS1